Provisioning For New Entrepreneurs Using The Canvas Business Model In The Mlaras Village Business Group - Nuri Purwanto (KARYA ABDI, 2020)
Business canvas model is a model that sends and captures the value of a business consisting of 9 elements contained in the core of a business that is presented simply and easily understandable, the tighter business competition and the covid-19 virus outbreak has brought major changes in the economy and the real impact is on the MSME sector therefore STIE PGRI Dewantara Jombang is moved to conduct a community service program with the theme is training to create a business plan canvas model , simple and easy to apply creation there are three methods used in community service conducted this time, namely, a lecture model that presents about canvas business theory, the second model of baking practice as a form of implementation of value preposition and segmentation and the second is the presentation and discussion model to assess the level of understanding of the participants regarding the material that has been done before, the process of activities goes smoothly without being constrained , as well as the open insights of participants on the importance of making business planning before doing business